2016
DOI: 10.7243/2053-5775-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Current status of awareness, knowledge and attitude of dentists in palestine towards cone beam computed tomography: A survey

Abstract: Objectives: Cone Beam Computed Tomography (CBCT) is being seen by many in dentistry as the standard imaging procedure for many dental implants, orthognathic, orthodontic, or endodontic cases. With this understanding, the purpose of this study was to assess the current state of knowledge, attitude and awareness of dentists in Palestine towards the usage of CBCT. Materials and methods: An online questionnaire with 16 items on CBCT was mailed to 300 private practitioners registered with the Palestinian Dental Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A self-administered questionnaire was designed based on previous studies with some modi cations, assessing the knowledge, awareness, practice, education, and applications of CBCT among a convenient sample of pediatric dentists from private, governmental, and academic elds throughout Egypt. [12][13][14] The survey participants were chosen based on their experience in the practice of pediatric dentistry in Egypt. The participating pediatric dentists were ensured that the results of the study were con dential and were used only for scienti c purposes.…”
Section: Methodsmentioning
confidence: 99%
“…A self-administered questionnaire was designed based on previous studies with some modi cations, assessing the knowledge, awareness, practice, education, and applications of CBCT among a convenient sample of pediatric dentists from private, governmental, and academic elds throughout Egypt. [12][13][14] The survey participants were chosen based on their experience in the practice of pediatric dentistry in Egypt. The participating pediatric dentists were ensured that the results of the study were con dential and were used only for scienti c purposes.…”
Section: Methodsmentioning
confidence: 99%
“…An online questionnaire assessing the awareness of CBCT was sent by [12] to 300 Palestinian private dental practitioners registered with the Palestinian Dental Association. More than half the sample (176 dentists) responded; 110 failed to respond, and 14 could not be contacted.…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%
“…All respondents claimed an awareness of CBCT and stated their desire for more education on the subject and an expansion of its application in dentistry. They concluded that although there was a positive attitude towards CBCT amongst dental practitioners, their knowledge in the field was deficient [12].…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%
“…Thus, this study aimed to assess the knowledge level of Iranian dental practitioners regarding digital radiography and CBCT. In this cross-sectional study, a researcherdesigned questionnaire according to previous studies was used [8][9][10]. this questionnaire included three main domains of demographic information (age, gender, general or specialty practice, type of specialty, work experience), knowledge about digital radiography (advantages, disadvantages, physical properties), and knowledge about CBCT (indications, applications, advantages, route of knowledge acquisition).…”
Section: Introductionmentioning
confidence: 99%